Distal Oblique Bundle Reinforcement for Treatment of DRUJ Instability - Brink, Peter R. G.; Hannemann, Pascal F. W. (Journal of Wrist Surgery, 2015)
Background Chronic, dynamic bidirectional instability in the distal radioulnar joint (DRUJ) is diagnosed clinically, based on the patient's complaints and the finding of abnormal laxity in the vicinity of the distal ulna. In cases where malunion is ruled out or treated and there are no signs of osteoarthritis, stabilization of the DRUJ may offer relief. To this end, several different techniques have been investigated over the past 90 years.Materials and Methods In this article we outline the procedure for a new technique using a tendon graft to reinforce the distal edge of the interosseous membrane.Description of Technique A percutaneous technique is used to harvest the palmaris longus tendon and to create a tunnel, just proximal to the sigmoid notch, through the ulna and radius in an oblique direction. By overdrilling the radial cortex, the knotted tendon can be pulled through the radius and ulna and the knot blocked at the second radial cortex, creating a strong connection between the radius and ulna at the site of the distal oblique bundle (DOB). The tendon is fixed in the ulna with a small interference screw in full supination, preventing subluxation of the ulna out of the sigmoid notch during rotation.Results Fourteen patients were treated with this novel technique between 2011 and October 2013. The QuickDASH score at 25 months postoperatively (range 16–38 months) showed an improvement of 32 points. Similarly, an improvement of 33 points (67–34 months) was found on the PRWHE. Only one recurrence of chronic, dynamic bidirectional instability in the DRUJ was observed.Conclusion This simple percutaneous tenodesis technique between radius and ulna at the position of the distal edge of the interosseous membrane shows promise in terms of both restoring stability and relieving complaints related to chronic subluxation in the DRUJ.
Keywords: distal radioulnar joint; distal oblique bundle; instability; posttraumatic wrist disorder